Gambaran Pola Makan Pada Pasien Diabetes Mellitus Di Puskesmas Cempaka Putih Jakarta - Veronika Marpaung; Yohanes Gamayana Trimawang Aji; Yenny (Jurnal Kesehatan Mahardika, 2022)
Diabetes mellitus (DM) is a degenerative disease whose prevalence continues to increase worldwide. This can be seen from the medical record data obtained at thr cempaka putih  healt center, central Jakarta, diabetes  mellitus increased in 2021 as many as 3767 visits. This high incidence  is caused by several  things. One of them is the eating behavior of diabetes mellitus ptients in the working area of the cempaka putih  public health center. This study aims to determine the description of dietary behavior in patiens with diabetes mellitus. This research is a quantitative research is whit adescritive design. The number of samples in this study is 91 obtained through convecience  sampling and data collection using a questionnaire. The results of this study showed that the eating behavior of diabetes mellitus patients was very good as many as 70 people (76,9%). Suggestions are given so that every health worker can provide information on an ongoing basis to Diabetes Mellitus patients who seek treatment to be able to regulate their diet properly.